Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18485/epmj.2018.8.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Intellectual Capital Components on Project Performance

Abstract: In today's knowledge-based business environment, intellectual capital (IC) is considered as an important contributor to project success. The aim of this paper is to question whether and, if so how, IC components (human, structural and relational capitals) influence project performance in the banking sector. Results show that all components of IC matter for project performance. More precisely, results demonstrate that a fair proportion of project performance (49.9%) is accounted for human, structural and relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 16 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…These results had initially been envisioned, to a certain extent. It has previously been shown that human capital is one of the key innovation factors (Delgado-Verde et al, 2016;Rezende et al, 2017), as well as that it is crucial for competitiveness, efficiency, and innovation (Cebi et al, 2010;Firer & Stainbank, 2003;Milosevic et al, 2018;Pew Tan et al, 2007). Additionally, our findings are in line with Soewarno and Tjahjadi (2020) who argue that organizations that invest in human capital have a better prospect for innovations as well as R&D improvements.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results had initially been envisioned, to a certain extent. It has previously been shown that human capital is one of the key innovation factors (Delgado-Verde et al, 2016;Rezende et al, 2017), as well as that it is crucial for competitiveness, efficiency, and innovation (Cebi et al, 2010;Firer & Stainbank, 2003;Milosevic et al, 2018;Pew Tan et al, 2007). Additionally, our findings are in line with Soewarno and Tjahjadi (2020) who argue that organizations that invest in human capital have a better prospect for innovations as well as R&D improvements.…”
Section: Discussionsupporting
confidence: 88%
“…The knowledge management implementation improves resource efficiency and effectiveness and, consequently, an organization's performance and competitiveness (Cebi, Aydin, & Gozlu, 2010). It is proved that intellectual capital contributes to the profitability, efficiency, and earnings per share of organizations (Firer & Stainbank, 2003;Milosevic, Dobrota & Barjaktarovic Rakocevic, 2018;Pew Tan, Plowman & Hancock, 2007). Yen (2013) analyzed how human capital affects innovative capability in banks, while Gurbuz and Mert (2011) state that human resources receive increasing recognition worldwide, related to the strategy and performance measurement.…”
Section: Human Capitalmentioning
confidence: 99%
“…Methods. There are various indicators for assessing the level of digitalization of countries [15][16][17][18][19][20][21][22][23]. The Digital Economy and Society Index (DESI) [17] the only of the considered indices is calculating specifically for the EU countries.…”
Section: Object Of Researchmentioning
confidence: 99%
“…Parallel with the development of national economy and banking sector, project finance in Serbia has experienced a positive, rising trend, thereby attracting significant attention of researchers and academic community. Research of domestic market in the domain of project finance refers to risk evaluation of project finance in Serbia [2,3], potential and challenges of project finance of renewable energy sources [4], capital structure [5,6], analysis of methodologies of project finance and their applicability depending on the type of project [7], analysis of key factors of successful project realisation in family enterprises [8], project management in the public sector [9], influence of intellectual capital on project performances [10], etc. The paper aims to present and analyse the principles of project finance in the housing construction and point the challenges and potentials of this market segment.…”
Section: Introductionmentioning
confidence: 99%